2011
DOI: 10.1007/bf03404874
|View full text |Cite
|
Sign up to set email alerts
|

The Population Attributable Fraction of Asthma Among Canadian Children

Abstract: sthma is a leading cause of chronic illness among Canadian children. Quantifying the relative contributions of modifiable exposures to the development of Canadian childhood asthma may identify the most effective targets for individual and societal intervention and suggest future research targets. Our objective was to determine the population attributable fraction (PAF) of childhood asthma in Canada due to modifiable environmental exposures, including particulates, nitrogen dioxide (NO 2), environmental tobacco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…60 Data sources: In almost all the studies, the burden was estimated for countries or regions using official statistics. Two studies applied the CRA methodology to data (prevalence, costs) from survey samples , [43][44] Shin et al 45 estimated and applied the PAF in a cohort, Simons et al 79 Outcomes: The SHS-attributable burden of disease was mainly studied in terms of mortality (55.6% of the studies), followed by morbidity (33.3%), DALYs (22.2%) and costs (18.1%). Some studies investigated also the burden from hospital admissions or years of potential life lost (Table 1).…”
Section: Population Attributable Fraction: Inmentioning
confidence: 99%
“…60 Data sources: In almost all the studies, the burden was estimated for countries or regions using official statistics. Two studies applied the CRA methodology to data (prevalence, costs) from survey samples , [43][44] Shin et al 45 estimated and applied the PAF in a cohort, Simons et al 79 Outcomes: The SHS-attributable burden of disease was mainly studied in terms of mortality (55.6% of the studies), followed by morbidity (33.3%), DALYs (22.2%) and costs (18.1%). Some studies investigated also the burden from hospital admissions or years of potential life lost (Table 1).…”
Section: Population Attributable Fraction: Inmentioning
confidence: 99%
“…Reasons for this trend are currently unclear, but factors including lifestyle changes [13], environmental challenges (such as traffic-related pollution) [4], and tobacco smoke exposure [2, 5], dust mites [6], indoor dampness and molds [7], and pets [4] have been implicated. Additionally, household air pollution (HAP) from the use of biomass for cooking is increasingly being recognized as a risk factor for asthma and other respiratory symptoms, especially in low- and middle-income countries (LMIC) [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is a common chronic condition in children and remains the leading cause of childhood morbidity as measured by hospitalization and school absences (Garner and Kohen, ; Moonie et al., ; Simons et al., ). Currently, approximately 10% of Canadian children (aged 2–7 years) are diagnosed with asthma (Statistics Canada ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, approximately 10% of Canadian children (aged 2–7 years) are diagnosed with asthma (Statistics Canada ). While asthma prevalence continues to increase among children (Simons et al., ), the etiology of the disease is not firmly established. Generally, studies have found that lifestyle changes (Konstantaki et al., ; Rodriguez et al., ) and exposure to certain environmental agents (Han et al., ; Simons et al., ) are likely explanations for the apparent increase in prevalence.…”
Section: Introductionmentioning
confidence: 99%